Deconstructing American Values and Moralities in Wendy Wasserstein's an American Daughter - Eltantawy, Ghada Mahmoud Ibrahim (جامعة بورسعيد - كلية الآداب, 2020)
يدرس البحث تفكيك القيم والأخلاقيات الأمريكية في مسرحية ابنه أمريكية للكاتبة ويندي واسيرستين، وكيف يمكن تناول تلك المسرحية لواسيرستين كوسيلة لكشف التناقض البنيوي الذي يوجد في نواة المجتمع الأمريكي. ويقوم بعرض تلك القراءة من خلال استخدام مفهوم الفارماكون عند جاك دريدا. وتشير نتائج البحث إلى وجود ترابط بين أفكار واسترستين المشوشة ونهج دريدا التفكيكي.
This research studies the Deconstruction of American Values and Moralities in Wendy Wasserstein's An American Daughter. It examines how Wasserstein’s An American Daughter can be seen as a means of exposing the structural contradiction dwelling at the core of the American society. It anticipates such reading through the use of Jacques Derrida’s concept of Pharmakon. The results reveal the correlation between Wasserstein's disruptive thinking and Derrida's deconstructive approach.
Keywords: الفنون المسرحية -- المسرح الأمريكي -- المسرحيون الامريكيون -- مسرحية ابنة أمريكية -- واسبرستين ، ويلدي -- أمريكا